2011
DOI: 10.4315/0362-028x.jfp-10-108
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with food workers working while experiencing vomiting or diarrhea

Abstract: This study sought to determine the frequency with which food workers said they had worked while experiencing vomiting or diarrhea, and to identify restaurant and worker characteristics associated with this behavior. We conducted interviews with food workers (n = 491) and their managers (n = 387) in the nine states that participate in the Centers for Disease Control and Prevention's Environmental Health Specialists Network. Restaurant and worker characteristics associated with repeatedly working while experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 12 publications
2
39
1
1
Order By: Relevance
“…7 This document describes effective management of workers' health and hygiene through a number of practices, including hand washing procedures to reduce and remove foodborne pathogens; requirements for the use and maintenance of gloves and clean outer garments to reduce the transfer of pathogens from workers to food and other objects; and procedures for the identification and restriction of sick workers. 8,9 To ensure that workers follow these practices, restaurants rely predominantly on food safety training. 10,11 While worker training may increase knowledge of proper food safety practices -an important part of food safety control -a number of studies show that food safety training does not ensure that workers actually perform food safety behaviors.…”
mentioning
confidence: 99%
“…7 This document describes effective management of workers' health and hygiene through a number of practices, including hand washing procedures to reduce and remove foodborne pathogens; requirements for the use and maintenance of gloves and clean outer garments to reduce the transfer of pathogens from workers to food and other objects; and procedures for the identification and restriction of sick workers. 8,9 To ensure that workers follow these practices, restaurants rely predominantly on food safety training. 10,11 While worker training may increase knowledge of proper food safety practices -an important part of food safety control -a number of studies show that food safety training does not ensure that workers actually perform food safety behaviors.…”
mentioning
confidence: 99%
“…The absence of safety policies such as these is a food safety risk as infected staff could contaminate food and cause a wide spread of infection among students and colleagues. Sumner et al (2011) reported of a similar experience in the US where some staff reported to report to work with diarrhoea and vomiting symptoms due to absence of policies for staff to absent themselves when sick. This was different in Lincolnshire where all staff reported they most likely will report possible infections and were given or would be given some time off work to recover and avoid possible food contamination by their matrons.…”
Section: Staff Hygiene Practices and Food Lawmentioning
confidence: 81%
“…As socially desirable results could have been given in the face-to-face interview with a food safety inspector the actual number of food handlers working with GE may be even higher. Other studies reported that 5 per cent of the respondents in the Environmental Health Specialists Network telephone survey among food service workers in restaurants indicated that they had worked while sick with vomiting or diarrhea (Green et al, 2005), whereas in another study, 12 per cent of the interviewed food workers said they had worked while suffering vomiting or diarrhea on two or more shifts in the previous year (Sumner et al, 2011).…”
Section: Discussionmentioning
confidence: 95%